Metastatic malignant melanoma of unknown primary in temporalis muscle - Grech, Alexia (J Surg Case Rep, 2020)
Metastatic melanoma of unknown primary (MUP) is an uncommon melanocytic lesion found in distant sites with no evident skin involvement. This case report presents a 75-year-old woman who underwent local excision for a lump in the right temporal area, which had been present for 6 months and had been suspected to be a lipoma. Histology confirmed that the tissue excised from the temporalis muscle was composed of atypical, heavily pigmented melanocytes. Her history was negative for melanocytic lesions, and examination and extensive investigation including imaging had failed to identify a primary lesion. The patient is currently being followed up.